IDENTIFICATION OF PHYTOPLANKTON TYPES IN TAMBAK BANDENG WITH HIGH QUALITY OF OMEGA-3 - Herawati, Endang Yuli (JFMR (Journal of Fisheries and Marine Research), 2019)
Microalgae as a source of nutrients, can be a good alternative to the use of high-level organisms. The abundant omega 3 content in plankton, especially phytoplankton, needs to be conducted research on the identification of the types of phytoplankton in milkfish with high omega-3 quality. The purpose of the study was to identify the types of plankton containing omega-3 and to determine the levels of omega-3 from plankton found in milkfish ponds. This research was conducted at the Laboratory of the Faculty of Fisheries and Marine Sciences, Brawijaya University, Malang. The highest abundance of phytoplankton is from the Bachillariophyta division and the lowest division euglenophyta. Five types of plankton were determined to be tested for omega-3 fatty acids using the gas chromatography (GCMS) method, namely: Chaetoceros sp, Tetraselmis sp, Nitzchia, Chlorella and Spirulina. GCMS test results from several types of omega-3 fatty acid plankton isolates in Chaetoceros calcitrans were the highest compared to the other 4 plankton types. Conclusion of the composition of plankton in traditional pond waters consists of 4 phytoplankton divisions namely Chlorophyta, Chrysophyta, Cyanophyta, and Euglenophyta. GCMS test results from several types of plankton isolates omega-3 fatty acids in Chaetoceros sp, the highest compared to Tetraselmis sp, Nitzchia, Chlorella and Spirulina. Suggestion of natural feed in the water of milkfish ponds should use Chaetoceros sp because the content of omega 3 is high.Â Keywords: phytoplankton, omega-3Â